2018
DOI: 10.1016/j.jctube.2018.06.005
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of tuberculosis treatment outcomes among a retrospective cohort in rural, Central India

Abstract: IntroductionProgrammatic design affects access to healthcare and can influence tuberculosis treatment outcomes. Potential predictors of tuberculosis treatment outcomes in one rural Indian setting were examined to improve outcomes with a focus on access to care.MethodsRoutinely collected tuberculosis treatment data from Jan Swasthya Sahyog, a community based healthcare system in rural Chhattisgarh, India were examined from 2003–2015. Predictors were analyzed for associations with death, loss to follow-up or fai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 26 publications
0
4
1
2
Order By: Relevance
“…In Karamoja, HIV prevalence is lower than the national average [ 64 ] and as such, HIV is not a major determinant of TB and outcomes: only 4.5% of the study participants were HIV positive. In contrast to other studies [ 17 , 20 ] that had a higher HIV co-infection rate, HIV did not increase the risk of having an unsuccessful TB treatment outcome in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…In Karamoja, HIV prevalence is lower than the national average [ 64 ] and as such, HIV is not a major determinant of TB and outcomes: only 4.5% of the study participants were HIV positive. In contrast to other studies [ 17 , 20 ] that had a higher HIV co-infection rate, HIV did not increase the risk of having an unsuccessful TB treatment outcome in this study.…”
Section: Discussioncontrasting
confidence: 99%
“…3,20 . En este mismo sentido, otros autores reportan asociación entre bajo peso y muerte por todas las causas en pacientes con TBC 4,16,[26][27][28] . La alta mortalidad en este grupo de pacientes puede ser debida a la disminución de la inmunidad, ya que el bajo peso puede suprimir la estimulación linfocítica y reducir la secreción de citoquinas pro-inflamatorias 7,29,30 .…”
Section: Discussionunclassified
“…En otras palabras, esto lleva a producir un círculo vicioso sinérgico del estado nutricional adverso. En este mismo sentido existen reportes en los que se relaciona un mayor riesgo de muerte entre los pacientes con TBC y bajo peso 3,4 , por lo que debe considerarse un manejo nutricional del paciente complementario al tratamiento farmacológico contra la TBC [5][6][7] .…”
unclassified
“…Our analysis found that models using either distance measurement reached very similar conclusions, and therefore we recommend that in low-resource settings, the simpler measurement (Cartesian distance) should likely be more appropriate for routine programme use. For TB patients that were treated at the city's tertiary hospital (QECH), greater household to clinic distance might be a proxy for lack of access to quality health care service [8,19]. Individuals who live in the peri-urban areas far from the centre of Blantyre have limited resources for transport, and may struggle to access timely tertiary-level health care compared to those living nearer to the centre of the city [20].…”
Section: Discussionmentioning
confidence: 99%